2013
DOI: 10.4236/health.2013.59196
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between body mass index, thickness of subcutaneous fat, and the gluteus muscle as the intramuscular injection site

Abstract: An intramuscular injection (IMI) is an injection given directly into the central area of a specific muscle. Certain medicines need to be administered by the gluteal route for these to be effective. The aim of this study was to determine the influence of body mass index (BMI), subcutaneous fat, and muscular thickness of the dorsogluteal IMI site among healthy Japanese women. There were 39 healthy female subjects who volunteered and met the criteria. Their ages ranged from 40s to 60s (50.82 ± 6.04). With the dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 12 publications
(11 reference statements)
0
15
0
1
Order By: Relevance
“…[2,11,[44][45][46] Critical assessments of patient weight, BMI, gender and injection site, needle length, volume of medication before administering IM injections is important and therefore should drive practice change.…”
Section: Injection Depthmentioning
confidence: 99%
“…[2,11,[44][45][46] Critical assessments of patient weight, BMI, gender and injection site, needle length, volume of medication before administering IM injections is important and therefore should drive practice change.…”
Section: Injection Depthmentioning
confidence: 99%
“…Sakamaki et al [9] measured the Four and Three-way split positions of healthy subjects by ultrasonography. Their study showed that the mean value of the DEB were, in the case of persons with BMI of <21 kg/m 2 , 67.46 mm on the right buttocks, and 63.76 mm on the left buttocks, and, in the case of persons with BMI ≥ 21 kg/m 2 , were 73.34 mm on the right buttocks and 70.17 mm on the left buttocks.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, Yasuhara et al [5], Sakamaki et al [9], and Tanioka et al [10] measured by ultrasonography the optimal injection needle length for dorsogluteal IM injection sites among Japanese volunteer subjects. Similarly, Takahashi et al [11] measured the subcutaneous tissue thickness of Hochstetter's site.…”
Section: Introductionmentioning
confidence: 99%
“…Bu komplikasyonların çoğunda da uygulamanın dorsogluteal bölgeye yapıldığı bilinmektedir (36) . Literatürde kanıta dayalı çalışmalar, ventrogluteal bölgenin büyük kan damarları ya da sinirleri barındırmaması ve kemik dokusundan uzak olması nedenleri ile güvenle kullanılabileceğini gös-termektedir (37)(38)(39) . Fakat ülkemizde bu bölgenin kullanımı henüz yaygın değildir.…”
Section: Imventro-sim (Ventrogluteal Bölge Intramüsküler Ilaç Uygulamunclassified